The Archaeology of East Oxford - Griffiths, D; Harrison, J; Bayer, O (University of Oxford, 2020)
Heritage-Lottery Funded Archaeology and History Project on East Oxford, based at Oxford University Department for Continuing Education. Data derived from field, archive and historical research. Includes excavation reports (pdf) and data, geophysical survey data, GIS shape files, photographs, plans and spreadsheets. NB: For full access to the contents of this dataset, it is advised that Archeox.zip be extracted rather than simply opened following download, as there are two pdf files which may not open correctly if the zip is opened directly rather than extracted. Specifically, these files are: Chapter 0 - Monograph Open Access pdf: The Archaeology of East Oxford > Archeox Monograph Open Access.pdf and Chapter 2 - Archeox: the emergence of a community > Impact Evaluation Report.pdf.